(untitled) (American Journal of Business Management, Economics and Banking, 2024)
The authors of the article describe the main accounting methods that are used by enterprises, indicating their main regulatory and legal aspects.It is indicated how to correctly build an accounting system at an enterprise in modern conditions.The authors revealed that accounting must be maintained in order to monitor the financial position of the company and in order to be able to evaluate the results of its activities. Also, apply a simplified taxation system and maintain accounting records in accordance with the law.